INDEKS KONSERVATISME DALAM INTEGRITAS LAPORAN KEUANGAN: BERDASARKAN GOOD CORPORATE GOVERNANCE, REPUTASI KAP, LEVERAGE DAN AUDIT TENURE - Fitriah Puji Yanti; Veni Soraya Dewi (AKUNTANSI DEWANTARA, 2023)
The integrity of financial statements is very important for companies in order to gain the trust of users of financial statements. This study aims to analyze the effect of good corporate governance, reputation, leverage and audit tenure on the integrity of financial statements. 135 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020 became the population and 15 were selected as samples by purposive sampling. This research method uses a quantitative approach with data analyzed using multiple linear regression analysis. Audit committee variables and audit tenure variables have a positive effect on the integrity of financial statements, managerial ownership and CPA reputation variables have a negative effect on the integrity of financial statements, while the independent commissioner, institutional ownership and leverage have no effect on the integrity of financial statements. This study implies that in manufacturing companies the factors that are thought to affect the integrity of financial statements in this study still show different results from previous studies so that they cannot be generalized in various sectors and research periods. These factors still need to be re-examined in further research to get more valid results.